1
$\begingroup$

I am trying to compute the Laurent expansion of $\frac{x}{x-1}$ around $\alpha=2$. I wrote it out as a partial fraction expansion so we have: $$ \frac{x}{x-1} = 1 + \frac{1}{x-1} = 1-\frac{1}{1-x} $$ And so we should have the Laurent expansion of this by the geometric series obtaining: $$ 1-\sum_{n=0}^\infty (x-2)^n = -(x-2)-(x-2)^2-\cdots $$ But this is wrong, according to the textbook I am working with the correct answer should be: $$ 2-(x-2)+(x-2)^2-(x-2)^3+\cdots $$ I don't know where exactly I've gone wrong either, I suspect I've made a mistake in computing the expansion at $\alpha=2$ because I know that when $\alpha=0$ this would have given the correct result. I'd just like to understand where I went wrong, I think I am misunderstanding something critical.

$\endgroup$
2
  • $\begingroup$ Do you expect us to guess where you made a mistake ? $\endgroup$
    – user65203
    May 13, 2019 at 13:14
  • $\begingroup$ @YvesDaoust Sorry if the question wasn't formulated better. I thought it was clear that I had a misunderstanding on how exactly we move from computing a Laurent series expansion at $\alpha=0$ to an arbitrary point. I believe that was where my mistake was, but I didn't understand where the method I used didn't work... seemed like a reasonable enough question to me. $\endgroup$
    – Ltoll
    May 13, 2019 at 13:17

2 Answers 2

3
$\begingroup$

$1+\dfrac1{x-1} =1+\dfrac1{1+(x-2)}=1+1-(x-2)+(x-2)^2-(x-2)^3+...$

$\endgroup$
1
$\begingroup$

You went wrong when you wrote that$$\frac1{1-x}=\sum_{n=0}^\infty(x-2)^n.$$The sum of this series is actually$$\frac1{1-(x-2)}=\frac1{3-x}.$$

$\endgroup$

You must log in to answer this question.

Not the answer you're looking for? Browse other questions tagged .